(untitled) (Revista Electrónica REDINE, 2018)
This article refers to an investigation which had objective to improve the communication and to decrease the conflicts into the educational field, in special manner on university professors where alternative means are required to resolve divergences such as Mediation. It’s framed in a field investigation of descriptive character. It proposes qualification to the resolution of classrooms’ conflicts. The subjects of study were conformed by 45 teachers of the institution, to whom the technique of the survey was applied through an instrument of questionnaire type, previous validation and self’s confidence. With the results it was managed to demonstrate the necessity to realise a qualification work about Educational Mediation, oriented to the teachers of the Veterinary Sciences Deanship that entail to strengthen through team work, academic efforts that are required to improve the resolution of classroom’s conflict.